Investigating the role of mechanosensitive channel Piezo1 in the CNS - VELASCO ESTEVEZ, MARIA (Trinity College Dublin. School of Medicine. Discipline of Physiology, 2019)
All cells in the organism are able to sense changes in the mechanical properties of their environment, translating them into chemical intracellular signals through a process termed mechanotransduction, mostly via mechanoreceptors. Piezo1 (Fam38A, Mib) is a mechanosensitive channel from the PIEZO family. It is one of the largest protein described so far, consisting of more than 2,500 amino acids and forming a 900kDa each monomer. Piezo1 associates in homotrimers and allows rapidly inactivated currents upon membrane stretch activation. It is largely conserved among species and its expression has been studied in lung, kidney, bladder, skin, endothelium, red blood cells and retinal ganglia cells; but little is known about Piezo1 in the CNS. Studies in the literature have reported that Piezo1 is expressed in the basal membrane of neurons under physiological conditions, but absent in astrocytes. In this study, we show that the expression of Piezo1 in astrocytes can be induced under certain inflammatory stimuli such as LPS, psychosine and amyloid-β42 treatment. Piezo1 is located in the endoplasmic reticulum of astrocytes in such conditions, and its modulation by the activator Yoda-1 or inhibitor GsMTx4 regulates the levels of proinflammatory cytokines, astrocytic migration and Ca2+ signalling. Furthermore, we show that Piezo1 is induced in the astrocytes around the amyloid plaques of the Alzheimer s rat model TgF344-AD, in the same subcellular expression to what observed in vitro, supporting our previous findings. In addition, previous studies in our group have shown that Piezo1 is expressed on the highly myelinated tracts of the CNS, i.e. corpus callosum, arbor vitae and optic tract, suggesting that Piezo1 may somehow be implicated in the regulation of myelination. Here, we investigated the effects of modulating Piezo1 in the myelin state using both an ex vivo model with organotypic slice culture and an in vivo model of LPC-induced focal demyelination in mice. We demonstrate that activation of Piezo1 induces demyelination in slices, while inhibition with GsMTx4 leads to the opposite effect. Interestingly, GsMTx4 prevents the LPC-induced demyelination in vivo as well as preventing microglia reactivity and astrocytic death. Altogether, our results suggest a novel role of Piezo1 in the CNS, regulating astrocytic reactivity in inflammatory and/or toxic conditions, as well as in regulating the myelin state of the CNS.
APPROVED
Keywords: Piezo1; mechanoreceptors; Central nervous system; myelination; astrocytes; Alzheimer's Disease